2023
DOI: 10.7759/cureus.37443
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Pharmacological Therapies to Reduce Alcohol Consumption in Severe Alcohol-Related Hepatitis Patients: A Case Report

Abstract: Alcohol-related hepatitis (ARH) is an inflammatory liver disease caused by excessive alcohol intake over time. This represents a major health burden with a high mortality and poor prognosis. Reducing alcohol consumption is key to improving health outcomes and long-term mortality. Therefore, various measures have been implemented to aid in the reduction of alcohol consumption. On a population level, this includes minimum unit pricing to reduce alcohol purchases. On a patient level, evidence-based psychosocial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Alcohol dependence syndrome caused by drinking is also an important psychosocial problem, which is one of the common diseases in psychiatry ( 10 ). It has a high incidence rate, great harm, easy recurrence, and other characteristics, causing a serious economic and psychological burden on families and society ( 11 ). Research has shown that patients with alcohol dependence syndrome generally have depressive emotions and are not easily identifiable, increasing the risk of suicide for patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dependence syndrome caused by drinking is also an important psychosocial problem, which is one of the common diseases in psychiatry ( 10 ). It has a high incidence rate, great harm, easy recurrence, and other characteristics, causing a serious economic and psychological burden on families and society ( 11 ). Research has shown that patients with alcohol dependence syndrome generally have depressive emotions and are not easily identifiable, increasing the risk of suicide for patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%